Amine‐Substituted Diazocine Derivatives – Synthesis, Structure, and Photophysical Properties. Issue 11 (8th November 2018) - Gregory, Mark A.; Zhang, Bolong; Tilley, Andrew J.; Scheerlinck, Tamika; White, Jonathan M.; Wong, Wallace W. H.
Abstract: A series of amine‐substituted diazocines were synthesized in three steps from methyl 2‐aminobenzoate or methyl 3‐aminonaphtholate. The saddle‐shaped diazocine compounds showed similar interplane angle of 75° despite the different steric bulk of the amine substituents. In electrochemical experiments, these diazocines showed irreversible reduction most likely producing indolo[3, 2‐ b ]indoles rather than forming the 10‐electron planar aromatic species. The carbazole‐substituted naphthodiazocines showed the most interesting photophysical properties with evidence of transition from the saddle‐shaped ground state to a planar excited state geometry. Abstract :